Absence of Wdr13 Gene Predisposes Mice to Mild Social Isolation – Chronic Stress, Leading to Depression-Like Phenotype Associated With Differential Expression of Synaptic Proteins - Mitra, Shiladitya; Sameer Kumar, Ghantasala S.; Jyothi Lakshmi, B.; Thakur, Suman; Kumar, Satish (Frontiers in Molecular Neuroscience, 2018)
We earlier reported that the male mice lacking the Wdr13 gene (Wdr13-/0) showed mild anxiety, better memory retention, and up-regulation of synaptic proteins in the hippocampus. With increasing evidences from parallel studies in our laboratory about the possible role of Wdr13 in stress response, we investigated its role in brain. We observed that Wdr13 transcript gets up-regulated in the hippocampus of the wild-type mice exposed to stress. To further dissect its function, we analysed the behavioural and molecular phenotypes of Wdr13-/0 mice when subjected to mild chronic psychological stress, namely; mild (attenuated) social isolation. We employed iTRAQ based quantitative proteomics, real time PCR and western blotting to investigate molecular changes. Three weeks of social isolation predisposed Wdr13-/0 mice to anhedonia, heightened anxiety-measured by Open field test (OFT), increased behaviour despair- measured by Forced swim test (FST) and reduced dendritic branching along with decreased spine density of hippocampal CA1 neurons as compared to wild-type counterparts. This depression-like-phenotype was however ameliorated when treated with anti-depressant imipramine. Molecular analysis revealed that out of 1002 quantified proteins (1% FDR, at-least 2 unique peptides), strikingly, a significant proportion of synaptic proteins including, SYN1, CAMK2A and RAB3A were down-regulated in the socially isolated Wdr13-/0 mice as compared to its wild-type counterparts. This was in contrast to the elevated levels of these proteins in non-stressed mutants as compared to the controls. We hypothesised that a de-regulated transcription factor upstream of the synaptic genes might be responsible for the observed phenotype. Indeed, in the socially isolated Wdr13-/0 mice, there was an up-regulation of GATA1 - a transcription factor that negatively regulates synaptic genes and has been associated with Major Depression (MD) in humans. The present study demonstrates significant genotype x enviornment interaction for Wdr13 gene as shown by the reversal in the expression levels of several synaptic proteins in the mutant vis-à-vis wild-type mouse when exposed to social isolation stress.